The impact of digital infrastructure on urban total factor carbon emission performance: evidence from enterprise production and household consumption in China - Zhongxin, Yang; Shanshan, Huang; Jing, Ma; Ceyuan, Song; Shujing, Xu (Frontiers in Environmental Science, 2025)
Digital infrastructure, serving as the fundamental carrier of data elements, allows China to balance economic growth with reduced carbon intensity, opening new pathways for sustainable economic development globally. This study employs a Difference-in-Differences (DID) approach to investigate the impact of digital infrastructure on urban total factor carbon emission performance, and extend the research perspective to a micro level, focusing on mechanisms involving household consumption and enterprise production. The results demonstrate that (1) Digital infrastructure can enhances urban carbon performance by promoting green product innovation of enterprises and changing consumers’ consumption patterns (2) Heterogeneity analysis indicates that cities with higher income and educational levels among residents experience a more significant improvement in carbon performance, and digital infrastructure’s impact varies when combined with enterprise characteristics and technological capabilities, with non-state-owned enterprises and high-tech enterprises having relatively higher carbon-saving effects. The research results of this paper emphasize role of micro-subjects in the process of digital infrastructure affecting total-factor carbon emission performance, which has important theoretical and practical significance for guiding future economic policies and strategies.